Key characterization and evaluation descriptors: methodologies for the assessment of 22 crops - Alercia, A. (Bioversity International, 2011)
Bioversity International, with the financial support of the Global Crop Diversity Trust (the Trust) has led the development of strategic key sets of characterization and evaluation descriptors for 22 crops included in Annex I of the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA). The strategic sets of data standards are designed to facilitate access to and utilization of plant genetic resources information. Together with passport information, descriptors are critical to the effective sharing of evaluation data and to the efficient use of plant genetic resources. Passport, characterization and evaluation descriptors are included on the GENESYS portal, to facilitate access to information and promote the utilization of germplasm accessions.